Penggunaan Formula Grafik Fry untuk Menganalisis Keterbacaan Wacana Mahasiswa PGSD - Hidayati, Panca Pertiwi; Ahmad, Arifin; Inggriyani, Feby (Universitas Pendidikan Indonesia, 2018)
Elementary school teacher candidates should be able to develop good teaching materials based on student’s age they teach. In fact, it is frequently found that elementary school teacher candidates write their papers only by copying from books or the internet. It is rarely found that they are able to develop and synthesize the materials they cited with their own vocabulary in their paper. The purpose of this study is to describe the benefits of using the Fry graph formula in analyzing the legibility of materials of PGSD students works which is made for elementary school teaching materials. This study used the descriptive qualitative method. The results of the data analysis revealed student discourse that is not appropriate because of the lower level of legibility is 4 discourses (13.33%), which appropriate to its legibility is 8 discourses (26.67%), and those that are not appropriate because the higher level of legibility is 18 discourses (60%).